Inovasi Teknologi dalam Manajemen Kesehatan: Pemanfaatan Sistem Informasi Kesehatan Elektronik di Rumah Sakit - Carlof Carlof; Dety Mulyanti (Journal of Management and Social Sciences, 2023)
This kind of information system is developing so rapidly in all fields including in the health field. One of the evidence of the development of information systems especially in hospitals is electronic medical records. Thus, by folding electronic medical records with application or web bases will minimize the leakage of patient data to the general public. In addition, the use of these electronic medical records will make it easier for patients to register or access hospital services. The study uses a review literature study approach with several selected sources based on the established inclusion and exclusion criteria